Intranasal Premedication Effect of Dexmedetomidine Versus Midazolam on the Behavior of 2-6-Year-Old Uncooperative Children in Dental Clinic - Mahdavi, Alireza (J Dent (Tehran), 2018)
OBJECTIVES: The aim of this study was to compare the intranasal premedication effect of newly introduced dexmedetomidine (DEX) versus midazolam on the behavior of uncooperative children in the dental clinic. MATERIALS AND METHODS: This crossover double-blind clinical trial was conducted on 20 uncooperative children aged 2–6 years who required at least two similar dental treatment visits. The subjects were randomly given 1 μg/kg of DEX and 0.5 mg/kg of midazolam via the intranasal route. For the sedation protocol in the two groups, 0.25 mg/kg of atropine in combination with 0.5 mg/kg of midazolam added to 1–2 mg/kg of ketamine were used 30 minutes after premedication and transferring the patient to the operating room. Dental treatments were carried out by a pediatric dentist blinded to the type of the administered premedication. The sedative efficacy (overall success rate) of the agents was assessed by two independent pediatric dentists based on the Houpt scale. Data analyses were carried out according to Wilcoxon signed-rank test and paired t-test. RESULTS: There were no significant differences in the premedication efficacy of intranasal DEX and midazolam according to the Houpt scale (P>0.05). CONCLUSIONS: Intranasal midazolam and DEX are satisfactory and effective premedication regimens for uncooperative children.